PELATIHAN PEMBUATAN KEMPLANG BAWANG MERAH SEBAGAI PRODUK UNGGULAN LOKAL DI DESA REJOSO NGANJUK - Nita Cahyani; Suttrisno; Nur Inda Nafa Natalia; Ana Alfina (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
Entering the age of globalization can be said everything is modern. Many people want to become entrepreneurs. Actually, in the economic field, the average Rejoso Village community already has UMKM, but when there are ups and downs or failures they will feel depressed and desperate, instead of finding a solution they will go out of business and Switch other professions. Which causes people to be afraid of entrepreneurship again because of limited capital. In this case, students innovate to create a product that can help restore the entrepreneurial spirit of the village community. By utilizing the existing potential of processing shallots into processed snack products that have a distinctive taste with a combination of red onion toppings, so that this product can be easily imitated by villagers, making it easy enough and affordable capital. This study aims to provide added value and increase / extend the production of shallots which are basically shallots are only used as cooking ingredients. This research is descriptive with quantitative approach. The results of this study indicate that this type of kebame food product can be accepted by the surrounding community and will be developed by businesses in the village. And with its human resources, most of whom work as entrepreneurs, with the existence of these businesses, it can reduce the number of unemployed people.